Brief Report: Childhood‐Onset Systemic Necrotizing Vasculitides: Long‐Term Data From the French Vasculitis Study Group Registry. Issue 7 (July 2015) - Iudici, Michele; Puéchal, Xavier; Pagnoux, Christian; Quartier, Pierre; Agard, Christian; Aouba, Achille; Büchler, Matthias; Cevallos, Ramiro; Cohen, Pascal; de Moreuil, Claire; Guilpain, Philippe; Le Quellec, Alain; et al.
<x xml:space="preserve">Abstract</x> Objective To describe the initial features and long‐term outcomes of childhood‐onset small vessel and medium vessel systemic necrotizing vasculitides (SNVs), including antineutrophil cytoplasmic antibody–associated vasculitides (AAVs) and polyarteritis nodosa (PAN). Methods Data on patients with childhood‐onset SNV registered in the French Vasculitis Study Group database were reviewed for demographic characteristics, clinical, laboratory, and histologic features, and outcomes. Disease activity was assessed with the Birmingham Vasculitis Activity Score and the Paediatric Vasculitis Activity Score, and damage was scored using the Vasculitis Damage Index. Relapse and survival rates and causes of death were analyzed. Results Fifty‐six patients (35 with AAV and 21 with PAN) (median age at database enrollment 14 years [range 2–17]) were included in the study. The median duration of followup was 96 months (range 1–336); two‐thirds of the patients were followed up beyond 18 years of age. Six patients (11%) died, mostly of SNV‐related causes. Relapse rates ranged from 33% for microscopic polyangiitis to 50% for eosinophilic granulomatosis with polyangiitis (Churg‐Strauss) and 83% for granulomatosis with polyangiitis (Wegener's), with similar rates among AAV and PAN patients (76% and 75%, respectively); neither overall survival nor relapse‐free survival differed significantly between the 2 disease groups. Rates of relapse increased after 18 years of age, both among patients with AAV and among patients with PAN. At the last followup evaluation, AAV patients had more major flares and more severe accrued damage compared with PAN patients. Conclusion Despite similar relapse rates, patients with childhood‐onset AAVs experienced more major flares with more cumulative damage than those with pediatric PAN. Treatments aimed at reducing the rates of mortality and relapse in this patient group need to be developed and assessed.